Interactions between cannabis and schizophrenia in humans and rodents - Moustafa, Ahmed A.; Salama, Mohamed; Peak, Roseanne; Tindle, Richard; Salem, Amir; Keri, Szabolcs; Misiak, Błażej; Frydecka, Dorota; Mohammad, Wael (De Gruyter, 2017)
In this review, we provide an overview of the relationship between cannabis use and the development of schizophrenia, using both animal and human studies. We further discuss the potential neural mechanism that may mediate the relationship between cannabis use and schizophrenia symptoms. We finally provide clinical implications and future studies that can further elucidate the relationship between cannabis and schizophrenia.